Phosphorus-carbon negative electrode material, preparation method and application thereof

By preparing a phosphorus-carbon anode material with a double-shell core-shell structure, the core contains elemental phosphorus, sodium fluoride, and silicon oxide, while the outer shell is a carbon shell. This solves the problem of insufficient performance of hard carbon materials in sodium-ion batteries, achieving high specific capacity, excellent cycle stability, and high rate performance, making it suitable for industrial production.

CN120690832BActive Publication Date: 2026-11-06JIANGSU PYLON BATTERY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510838866.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-23
Publication Date
2026-11-06
Estimated Expiration
2045-06-23

AI Technical Summary

Technical Problem

Existing hard carbon materials have insufficient rate performance, specific capacity and cycle stability in sodium-ion batteries. The large volume change of elemental phosphorus during cycling affects the stability of the SEI film, and existing preparation methods are difficult to scale up for industrial production.

Method used

The phosphorus-carbon anode material adopts a double-shell core-shell structure. The core contains elemental phosphorus, sodium fluoride and silicon oxide, and the outer layer is a carbon shell formed by asphalt and organic carbon source. It is prepared by solid-phase mixing and gas-phase coating methods. Elemental phosphorus is deposited inside the carbon material, and sodium fluoride and silicon oxide improve the stability of the material.

Benefits of technology

It improves the specific capacity, cycle stability, and rate performance of phosphorus-carbon anode materials, reduces the expansion effect during cycling, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005461477690000151
    Figure BDA0005461477690000151
Patent Text Reader

Abstract

The application provides a phosphorus-carbon negative electrode material and a preparation method and application thereof, and relates to the field of electrochemical energy storage materials.The phosphorus-carbon negative electrode material has a double-shell core-shell structure; the inner core of the phosphorus-carbon negative electrode material comprises phosphorus, sodium fluoride and silicon oxide; the double shell comprises a first carbon shell layer and a second carbon shell layer from inside to outside, the first carbon shell layer is a carbon shell layer formed by decomposition of pitch; and the second carbon shell layer is a carbon shell layer formed by gas-phase coating of organic carbon source gas.The phosphorus-carbon negative electrode material has high specific capacity, excellent cycle stability and high rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochemical energy storage materials, and in particular to a phosphorus-carbon anode material, its preparation method, and its application. Background Technology

[0002] With the rapid development of renewable energy, the demand for efficient and long-life energy storage devices is increasing. Hard carbon materials, due to their unique structure and excellent sodium storage performance, have shown great potential in sodium-ion batteries. However, traditional hard carbon materials still need improvement in rate performance, specific capacity, and cycle stability. Based on the high capacity advantage of phosphorus-carbon materials, developing improved phosphorus-carbon anode materials with high rate performance and high stability holds great promise.

[0003] Existing technologies use carbon materials to directly react with phosphates to deposit elemental phosphorus. The reaction is concentrated on the surface of the carbon materials, and the deposition of elemental phosphorus is also mainly on the surface of the carbon materials. Since phosphorus undergoes large volume changes during cycling and deintercalation, it will affect the stability of the SEI film and the battery life.

[0004] To address this issue, it is necessary to deposit elemental phosphorus inside the particles and modify the material surface, which can greatly alleviate the expansion problem during cycling. Existing phosphorus-carbon materials mainly involve three methods: first, solid-phase mixing, where the reaction of phosphorus and carbon cannot guarantee phosphorus deposition inside the carbon, and the expansion of the phosphorus material during cycling can damage the SEI film, affecting cycle life; second, vapor deposition, which is costly and more suitable for laboratory operations, but difficult to scale up for industrial production; and third, solution or gel methods, which require sophisticated equipment for industrial-scale production.

[0005] In view of this, the present invention is hereby proposed. Summary of the Invention

[0006] The purpose of this invention is to provide a phosphorus-carbon anode material, its preparation method, and its application. The phosphorus-carbon anode material of this invention has high specific capacity, excellent cycle stability, and high rate performance.

[0007] To achieve the above objectives, the following technical solution is proposed:

[0008] In a first aspect, the present invention provides a phosphorus-carbon anode material, wherein the phosphorus-carbon anode material exhibits a double-shell core-shell structure;

[0009] The core of the phosphorus-carbon anode material includes elemental phosphorus, sodium fluoride, and silicon oxide.

[0010] The double shell consists of a first carbon shell and a second carbon shell, from the inside out. The first carbon shell is formed by the decomposition of asphalt, and the second carbon shell is formed by the gas of an organic carbon source being coated in the gas phase.

[0011] Preferably, the raw materials for preparing the core include sodium monofluorophosphate and silicon dioxide.

[0012] Preferably, the mass ratio of sodium monofluorophosphate to silicon dioxide is (7-9):(1-3).

[0013] Preferably, the organic carbon source gas is a mixture of acetylene and cyclohexane.

[0014] Preferably, the volume ratio of acetylene to cyclohexane is (8-5):(2-5).

[0015] Preferably, the particle size of the kernel is 0.5 to 5 μm.

[0016] Preferably, the thickness of the first carbon shell is 2–10 μm.

[0017] Preferably, the thickness of the second carbon shell is 0.3 to 1 μm.

[0018] In a second aspect, the present invention provides a method for preparing the phosphorus-carbon anode material as described in the first aspect, the method comprising:

[0019] Sodium monofluorophosphate, silica, and asphalt are mixed to obtain a mixture;

[0020] The mixture is subjected to a first sintering and a second sintering in sequence, and the carbon shell layer formed by the decomposition of asphalt is obtained to obtain sintered material one.

[0021] The first sintered material is subjected to a third sintering process. Sodium monofluorophosphate is first decomposed into phosphorus oxide and sodium fluoride. The phosphorus oxide reacts and deposits with the carbon shell to form elemental phosphorus, thus obtaining the second sintered material.

[0022] An organic carbon source gas is introduced into the sintered material 2 for gas-phase coating to obtain the phosphorus-carbon anode material.

[0023] Preferably, the mixing specifically includes:

[0024] Sodium monofluorophosphate and silicon dioxide are first mixed to obtain mixture one; then mixture one is mixed with asphalt to obtain mixture two.

[0025] Preferably, the mixture comprises, by mass percentage: 70-90% sodium monofluorophosphate and 10-30% silicon dioxide.

[0026] Preferably, the silicon oxide comprises silicon monoxide and / or silicon dioxide.

[0027] Preferably, the second mixture comprises, by mass percentage: 75-90% of the first mixture and 10-25% of asphalt.

[0028] Preferably, the first sintering, the second sintering, the third sintering, and the gas phase coating are all carried out under a protective gas atmosphere.

[0029] Preferably, the protective gas atmosphere includes any one of nitrogen, argon, or helium.

[0030] Preferably, the temperature of the first sintering is 100-150°C; and the time of the first sintering is 0.5-1 hour.

[0031] Preferably, the temperature of the second sintering is 500–800°C; and the time of the second sintering is 2–4 hours.

[0032] Preferably, the phosphorus oxide includes phosphorus pentoxide and / or phosphorus trioxide, with phosphorus pentoxide being the most preferred.

[0033] Preferably, the temperature of the third sintering is 800–1200°C; and the time of the third sintering is 2–4 hours.

[0034] Preferably, the organic carbon source gas is a mixture of acetylene and cyclohexane.

[0035] Preferably, the total flow rate of the organic carbon source gas is 10-50 mL / min.

[0036] Preferably, the flow rate ratio of acetylene to cyclohexane is (8-5):(2-5).

[0037] Preferably, the temperature of the gas phase coating is 600–900°C, and the time of the gas phase coating is 0.5–2 hours.

[0038] Thirdly, the present invention provides an application of the phosphorus-carbon anode material as described in the first aspect in the preparation of anode sheets or sodium-ion batteries.

[0039] Fourthly, the present invention provides a negative electrode sheet, the negative electrode sheet comprising a metal foil and a negative electrode coating; wherein the negative electrode coating comprises a phosphorus-carbon negative electrode material as described in the first aspect.

[0040] Fifthly, the present invention provides a sodium-ion battery, the sodium-ion battery comprising the negative electrode sheet as described in the fourth aspect.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] (1) The phosphorus-carbon anode material of the present invention presents a core-shell structure with two shells. The core of the phosphorus-carbon anode material includes elemental phosphorus, sodium fluoride and silicon oxide. Elemental phosphorus is deposited inside the asphalt shell, which greatly reduces the expansion effect of the material during cycling. Sodium fluoride can supplement sodium and further improve the first-time efficiency of the material. Silicon oxide acts as a framework material for high-temperature stability. The first carbon shell is a stable and uniform carbon layer formed by asphalt. The second carbon shell is a carbon shell formed by the gas of an organic carbon source through gas phase coating, which can reduce the specific surface area of ​​the material, improve irreversible surface reactions, and enhance the first-time efficiency and cycling performance.

[0043] (2) The preparation method described in this invention uses a solid-phase mixing method for sintering and a core-shell structure for preparing phosphorus-carbon materials. This method is easy to scale up, and phosphorus can be deposited inside the carbon material, which greatly reduces the expansion effect of the material during the cycle. Detailed Implementation

[0044] The embodiments and examples of the present invention will be described in detail below. However, those skilled in the art will understand that the following embodiments and examples are for illustrative purposes only and should not be considered as limiting the scope of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention. Unless otherwise specified, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0045] In a first aspect, the present invention provides a phosphorus-carbon anode material, wherein the phosphorus-carbon anode material exhibits a double-shell core-shell structure;

[0046] The core of the phosphorus-carbon anode material includes elemental phosphorus, sodium fluoride, and silicon oxide.

[0047] The double shell consists of a first carbon shell and a second carbon shell, from the inside out. The first carbon shell is formed by the decomposition of asphalt, and the second carbon shell is formed by the gas of an organic carbon source being coated in the gas phase.

[0048] In this invention, the phosphorus-carbon anode material exhibits a double-shell core-shell structure. The core of the phosphorus-carbon anode material includes elemental phosphorus, sodium fluoride, and silicon dioxide. Elemental phosphorus is deposited inside the asphalt shell, greatly reducing the expansion effect during cycling. Sodium fluoride acts as a sodium supplement, further improving the material's initial efficiency. Silicon dioxide serves as a high-temperature stable material, acting as a framework. The first carbon shell is a stable and uniform carbon layer formed by asphalt, while the second carbon shell is a carbon shell formed by the gaseous encapsulation of an organic carbon source. This reduces the material's specific surface area, improves irreversible surface reactions, and enhances initial efficiency and cycle performance. Therefore, the phosphorus-carbon anode material of this invention possesses high specific capacity, excellent cycle stability, and high rate performance.

[0049] As an optional implementation, the raw materials for preparing the core include sodium monofluorophosphate and silicon dioxide.

[0050] In this invention, sodium monofluorophosphate and silicon dioxide are used as raw materials. The main advantages are as follows: Compared with the direct addition of phosphorus oxide and sodium fluoride, sodium monofluorophosphate decomposes into phosphorus oxide and sodium fluoride. The decomposition temperature of sodium monofluorophosphate is higher than the temperature at which asphalt becomes a stable carbon layer. This ensures that the phosphorus element deposited by the reaction of phosphorus oxide and carbon layer is inside the asphalt shell. As a high-temperature stable material, silicon dioxide can play a skeletal role when sodium monofluorophosphate decomposes, ensuring the stability of the core-shell structure. In addition, sodium fluoride can play a role in supplementing sodium, further improving the initial efficiency of the material.

[0051] As an optional implementation, the mass ratio of sodium monofluorophosphate to silicon dioxide is (7-9):(1-3);

[0052] Among them, "7 to 9" can be, for example, 7, 7.5, 8, 8.5, 9, etc.;

[0053] Among them, "1 to 3" can be, for example, 1, 1.5, 2, 2.5, 3, etc.

[0054] As an optional implementation, the organic carbon source gas is a mixture of acetylene and cyclohexane.

[0055] In this invention, a carbon layer is deposited on the surface using a mixture of acetylene and cyclohexane gas, which can further reduce the specific surface area of ​​the material, improve the irreversible reaction on the surface of the phosphorus-carbon anode material, and further enhance the first-efficiency and cycle performance.

[0056] As an optional implementation, the volume ratio of acetylene to cyclohexane is (8-5):(2-5);

[0057] Among them, "8 to 5" can be, for example, 8, 7.5, 7, 6.5, 6, 5.5, 5, etc.;

[0058] Among them, "2 to 5" can be, for example, 2, 2.5, 3, 3.5, 4, 4.5, 5, etc.

[0059] As an optional implementation, the particle size of the core is 0.5 to 5 μm, for example, it can be 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, etc.

[0060] As an optional implementation, the thickness of the first carbon shell is 2 to 10 μm, for example, it can be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc.

[0061] As an optional implementation, the thickness of the second carbon shell is 0.3 to 1 μm, for example, it can be 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, etc.

[0062] In a second aspect, the present invention provides a method for preparing the phosphorus-carbon anode material as described in the first aspect, the method comprising:

[0063] Sodium monofluorophosphate, silica, and asphalt are mixed to obtain a mixture;

[0064] The mixture is subjected to a first sintering and a second sintering in sequence, and the carbon shell layer formed by the decomposition of asphalt is obtained to obtain sintered material one.

[0065] The first sintered material is subjected to a third sintering process. Sodium monofluorophosphate is first decomposed into phosphorus oxide and sodium fluoride. The phosphorus oxide reacts and deposits with the carbon shell to form elemental phosphorus, thus obtaining the second sintered material.

[0066] An organic carbon source gas is introduced into the sintered material 2 for gas-phase coating to obtain the phosphorus-carbon anode material.

[0067] In this invention, a solid-state mixing method is used for sintering, and a core-shell structure is used to prepare phosphorus-carbon materials. The preparation method of the phosphorus-carbon anode material described herein is easy to scale up. Phosphorus can be deposited inside the carbon material, which greatly reduces the expansion effect of the material during cycling, avoids the problem that the expansion of the phosphorus material will damage the SEI film, and improves the cycle life.

[0068] As an optional implementation, the hybrid specifically includes:

[0069] Sodium monofluorophosphate and silicon dioxide are first mixed to obtain mixture one; then mixture one is mixed with asphalt to obtain mixture two.

[0070] As an optional implementation, based on the total mass of the first mixture as 100%, the first mixture comprises, by mass percentage, 70-90% sodium monofluorophosphate and 10-30% silicon dioxide.

[0071] As an optional implementation, the content of sodium monofluorophosphate in the first mixture is 70% to 90%, for example, it can be 70%, 72%, 74%, 75%, 76%, 78%, 80%, 82%, 84%, 85%, 86%, 88%, 90%, etc.

[0072] As an optional implementation, the content of silicon oxide in the first mixture is 10% to 30%, for example, it can be 10%, 12%, 14%, 15%, 16%, 18%, 20%, 22%, 24%, 25%, 26%, 28%, 30%, etc.

[0073] As an optional implementation, the silicon oxide includes silicon monoxide and / or silicon dioxide.

[0074] As an optional implementation, with the total mass of the second mixture being 100%, the second mixture comprises, by mass percentage, 75-90% of the first mixture and 10-25% of asphalt.

[0075] As an optional implementation, the content of mixture one in mixture two is 75% to 90%, for example, it can be 75%, 76%, 78%, 80%, 82%, 84%, 85%, 86%, 88%, 90%, etc.

[0076] As an optional implementation, the asphalt content in the second mixture is 10-25%, for example, it can be 10%, 12%, 14%, 15%, 16%, 18%, 20%, 22%, 24%, 25%, etc.

[0077] As an optional implementation, the first sintering, the second sintering, the third sintering, and the gas phase coating are all carried out under a protective gas atmosphere.

[0078] As an optional implementation, the protective gas atmosphere includes any one of nitrogen, argon, or helium.

[0079] As an optional implementation, the temperature of the first sintering is 100-150℃, for example, it can be 100℃, 105℃, 110℃, 115℃, 120℃, 125℃, 130℃, 135℃, 140℃, 145℃, 150℃, etc.

[0080] As an optional implementation, the first sintering time is 0.5 to 1 hour, for example, 0.5 hours, 0.6 hours, 0.7 hours, 0.8 hours, 0.9 hours, 1 hour, etc.

[0081] As an optional implementation, the temperature of the second sintering is 500-800℃, for example, 500℃, 550℃, 600℃, 650℃, 700℃, 750℃, 800℃, etc.

[0082] As an optional implementation, the second sintering time is 2 to 4 hours, for example, 2 hours, 2.2 hours, 2.4 hours, 2.5 hours, 2.6 hours, 2.8 hours, 3 hours, 3.2 hours, 3.4 hours, 3.5 hours, 3.6 hours, 3.8 hours, 4 hours, etc.

[0083] In this invention, the asphalt is softened and coated with sodium monofluorophosphate and silicon dioxide at a first sintering temperature (100-150°C), and then heated to a second sintering temperature (500-800°C). The asphalt decomposes and forms a relatively uniform carbon layer, which enhances structural stability, inhibits volume expansion, helps to form a thinner, denser, and more stable solid electrolyte interphase (SEI) film, and acts as a barrier to improve chemical stability.

[0084] As an optional implementation, the phosphorus oxide includes phosphorus pentoxide and / or phosphorus trioxide, preferably phosphorus pentoxide.

[0085] As an optional implementation, the temperature of the third sintering is 800-1200℃, for example, 800℃, 850℃, 900℃, 950℃, 1000℃, 1050℃, 1100℃, 1150℃, 1200℃, etc.

[0086] As an optional implementation, the third sintering time is 2 to 4 hours, for example, 2 hours, 2.2 hours, 2.4 hours, 2.5 hours, 2.6 hours, 2.8 hours, 3 hours, 3.2 hours, 3.4 hours, 3.5 hours, 3.6 hours, 3.8 hours, 4 hours, etc.

[0087] In this invention, at the temperature of the third sintering (800-1200°C), sodium monofluorophosphate first decomposes into phosphorus oxide and sodium fluoride. Subsequently, after the phosphorus oxide reacts with the carbon material, elemental phosphorus is deposited inside the carbon shell formed by the decomposition of pitch. The internal deposition of elemental phosphorus greatly reduces the expansion effect of the material during the cycle. The sodium fluoride obtained from the internal decomposition can play a role in replenishing sodium, while silicon oxide, as a high-temperature stable material, can play a skeletal role during the decomposition of sodium monofluorophosphate.

[0088] As an optional implementation, the organic carbon source gas is a mixture of acetylene and cyclohexane.

[0089] As an optional implementation, the total flow rate of the organic carbon source gas is 10 to 50 mL / min, for example, it can be 10 mL / min, 15 mL / min, 20 mL / min, 25 mL / min, 30 mL / min, 35 mL / min, 40 mL / min, 45 mL / min, 50 mL / min, etc.

[0090] As an optional implementation, the flow ratio of acetylene to cyclohexane is (8-5):(2-5);

[0091] Among them, "8 to 5" can be, for example, 8, 7.5, 7, 6.5, 6, 5.5, 5, etc.;

[0092] Among them, "2 to 5" can be, for example, 2, 2.5, 3, 3.5, 4, 4.5, 5, etc.

[0093] As an optional implementation, the temperature of the gas phase coating is 600-900℃, for example, it can be 600℃, 650℃, 700℃, 750℃, 800℃, 850℃, 900℃, etc.

[0094] As an optional implementation, the gas phase coating time is 0.5 to 2 hours, for example, it can be 0.5 hours, 0.6 hours, 0.8 hours, 1 hour, 1.2 hours, 1.4 hours, 1.5 hours, 1.6 hours, 1.8 hours, 2 hours, etc.

[0095] Thirdly, the present invention provides an application of the phosphorus-carbon anode material as described in the first aspect in the preparation of anode sheets or sodium-ion batteries.

[0096] Fourthly, the present invention provides a negative electrode sheet, the negative electrode sheet comprising a metal foil and a negative electrode coating; wherein the negative electrode coating comprises a phosphorus-carbon negative electrode material as described in the first aspect.

[0097] As an optional implementation, the negative electrode coating is formed by curing a negative electrode slurry; wherein the negative electrode slurry includes the phosphorus-carbon negative electrode material, carbon black, dispersant and binder described in the first aspect.

[0098] As an optional implementation, the mass ratio of the phosphorus-carbon anode material, carbon black, dispersant, and binder is (93-96.5):(0.7-2):(1.3-2):(1.5-3);

[0099] Among them, "93~96.5" can be, for example, 93, 94, 95, 96, 96.5, etc.;

[0100] Among them, "0.7~2" can be, for example, 0.7, 0.8, 1, 1.2, 1.4, 1.5, 1.6, 1.8, 2, etc.;

[0101] Among them, "1.3~2" can be, for example, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, etc.;

[0102] Among them, "1.5 to 3" can be, for example, 1.5, 1.6, 1.8, 2, 2.2, 2.5, 2.8, 3, etc.

[0103] As an optional implementation, the dispersant is sodium carboxymethyl cellulose (CMC).

[0104] As an optional implementation, the adhesive is styrene-butadiene rubber latex (SBR).

[0105] As an optional implementation, the metal foil is aluminum foil.

[0106] Fifthly, the present invention provides a sodium-ion battery, the sodium-ion battery comprising the negative electrode sheet as described in the fourth aspect.

[0107] The present invention will be further illustrated below with specific embodiments and comparative examples. However, it should be understood that these embodiments are merely for the purpose of more detailed illustration and should not be construed as limiting the present invention in any way.

[0108] Example 1

[0109] This embodiment provides a phosphorus-carbon anode material, the preparation method of which includes the following steps:

[0110] (1) Sodium monofluorophosphate and silicon dioxide are mixed in a mass ratio of 80%:20% to obtain mixture one;

[0111] (2) Under a nitrogen atmosphere, the mixture one and asphalt are mixed in a mass ratio of 80%:20% to obtain mixture two;

[0112] (3) Under a nitrogen atmosphere, the mixture 2 is first sintered at 120°C for 45 min to soften and coat the asphalt. Then, the temperature is raised to 650°C and sintered for 3 h to decompose the softened asphalt and form a uniform carbon layer. Then, the temperature is further raised to 1000°C and sintered for 3 h to decompose sodium monofluorophosphate into phosphorus oxide and sodium fluoride. After the phosphorus oxide reacts with the carbon material, phosphorus element is deposited inside to obtain a phosphorus-carbon anode material with a first carbon shell.

[0113] (4) Under a nitrogen atmosphere, at 750°C, a mixture of acetylene and cyclohexane gas (total flow rate of the mixture is 30 mL / min, and the flow rate ratio of acetylene to cyclohexane is 6:4) is introduced into the phosphorus-carbon anode material with the first carbon shell. The mixture is then coated for 1 hour to form a second carbon shell, thus obtaining a phosphorus-carbon anode material with a double shell.

[0114] The finished phosphorus-carbon anode material obtained in step (4) presents a core-shell structure with a double shell. The core of the phosphorus-carbon anode material includes elemental phosphorus, sodium fluoride, and silicon oxide. The double shell includes a first carbon shell and a second carbon shell from the inside out. The first carbon shell is formed by the decomposition of asphalt. The second carbon shell is formed by the gas phase coating of a mixture of acetylene and cyclohexane. The particle size of the core is 3 μm, the thickness of the first carbon shell is 7 μm, and the thickness of the second carbon shell is 0.6 μm.

[0115] Example 2

[0116] This embodiment provides a phosphorus-carbon anode material, the preparation method of which includes the following steps:

[0117] (1) Sodium monofluorophosphate and silicon dioxide are mixed in a mass ratio of 90%:10% to obtain mixture one;

[0118] (2) Under a nitrogen atmosphere, the mixture one and asphalt are mixed in a mass ratio of 75%:25% to obtain mixture two;

[0119] (3) Under a nitrogen atmosphere, the mixture 2 is first sintered at 100°C for 1 hour to soften and coat the asphalt. Then, the temperature is raised to 700°C and sintered for 2 hours to decompose the softened asphalt and form a uniform carbon layer. Then, the temperature is further raised to 1200°C and sintered for 2 hours to decompose sodium monofluorophosphate into phosphorus oxide and sodium fluoride. After the phosphorus oxide reacts with the carbon material, phosphorus element is deposited inside to obtain a phosphorus-carbon anode material with a first carbon shell.

[0120] (4) Under a nitrogen atmosphere, at 900°C, a mixture of acetylene and cyclohexane gas (total flow rate of the mixture is 10 mL / min, and the flow rate ratio of acetylene to cyclohexane is 5:5) is introduced into the phosphorus-carbon anode material with the first carbon shell, and gas phase coating is performed for 0.5 h to form a second carbon shell, thereby obtaining a phosphorus-carbon anode material with a double shell.

[0121] The finished phosphorus-carbon anode material obtained in step (4) presents a core-shell structure with a double shell. The core of the phosphorus-carbon anode material includes elemental phosphorus, sodium fluoride, and silicon oxide. The double shell includes a first carbon shell and a second carbon shell from the inside out. The first carbon shell is formed by the decomposition of asphalt. The second carbon shell is formed by the gas phase coating of a mixture of acetylene and cyclohexane. The particle size of the core is 1 μm, the thickness of the first carbon shell is 10 μm, and the thickness of the second carbon shell is 0.3 μm.

[0122] Example 3

[0123] This embodiment provides a phosphorus-carbon anode material, the preparation method of which includes the following steps:

[0124] (1) Sodium monofluorophosphate and silicon dioxide are mixed in a mass ratio of 70%:30% to obtain mixture one;

[0125] (2) Under a nitrogen atmosphere, the mixture one and asphalt are mixed at a mass ratio of 90%:10% to obtain mixture two;

[0126] (3) Under a nitrogen atmosphere, the mixture 2 is first sintered at 150°C for 0.5h to soften and coat the asphalt. Then, the temperature is raised to 550°C and sintered for 4h to soften the asphalt and form a uniform carbon layer. Then, the temperature is further raised to 850°C and sintered for 4h to decompose the sodium monofluorophosphate into phosphorus oxide and sodium fluoride. After the phosphorus oxide reacts with the carbon material, phosphorus element is deposited inside to obtain a phosphorus-carbon anode material with a first carbon shell.

[0127] (4) Under a nitrogen atmosphere, at 600°C, a mixture of acetylene and cyclohexane gas (total flow rate of the mixture is 50 mL / min, and the flow rate ratio of acetylene to cyclohexane is 8:2) is introduced into the phosphorus-carbon anode material with the first carbon shell, and gas phase coating is carried out for 2 hours to form a second carbon shell, thereby obtaining a phosphorus-carbon anode material with a double shell.

[0128] The finished phosphorus-carbon anode material obtained in step (4) presents a core-shell structure with a double shell. The core of the phosphorus-carbon anode material includes elemental phosphorus, sodium fluoride, and silicon oxide. The double shell includes a first carbon shell and a second carbon shell from the inside out. The first carbon shell is formed by the decomposition of asphalt. The second carbon shell is formed by the gas phase coating of a mixture of acetylene and cyclohexane. The particle size of the core is 5 μm, the thickness of the first carbon shell is 3 μm, and the thickness of the second carbon shell is 1 μm.

[0129] Example 4

[0130] This embodiment provides a phosphorus-carbon anode material. The only difference from Embodiment 1 is that in step (1), sodium monofluorophosphate and silicon dioxide are mixed in a mass ratio of 95%:5% to obtain mixture one; the other steps are completely consistent with Embodiment 1.

[0131] Example 5

[0132] This embodiment provides a phosphorus-carbon anode material. The only difference from Embodiment 1 is that in step (1), sodium monofluorophosphate and silicon dioxide are mixed in a mass ratio of 65%:35% to obtain mixture one; the other steps are completely consistent with Embodiment 1.

[0133] Example 6

[0134] This embodiment provides a phosphorus-carbon anode material. The only difference from Embodiment 1 is that in step (2), the mixture one is mixed with asphalt at a mass ratio of 95%:5% to obtain mixture two; the other steps are completely consistent with Embodiment 1.

[0135] Example 7

[0136] This embodiment provides a phosphorus-carbon anode material. The only difference from Embodiment 1 is that in step (2), the mixture one is mixed with asphalt at a mass ratio of 70%:30% to obtain mixture two; the other steps are completely consistent with Embodiment 1.

[0137] Example 8

[0138] This embodiment provides a phosphorus-carbon anode material. The only difference from Embodiment 1 is that in step (3), the mixture is directly heated to 650°C and sintered for 4 hours in a nitrogen atmosphere, and then the temperature is further increased to 1000°C and sintered for 3 hours; the other steps are completely the same as in Embodiment 1.

[0139] Example 9

[0140] This embodiment provides a phosphorus-carbon anode material. The only difference from Embodiment 1 is that, in step (4), acetylene gas is introduced only into the phosphorus-carbon anode material with the first carbon shell; the other steps are completely consistent with Embodiment 1.

[0141] Example 10

[0142] This embodiment provides a phosphorus-carbon anode material. The only difference from Embodiment 1 is that, in step (4), cyclohexane gas is introduced only into the phosphorus-carbon anode material with the first carbon shell; the other steps are completely consistent with Embodiment 1.

[0143] Comparative Example 1

[0144] This comparative example provides a phosphorus-carbon anode material, which differs from Example 1 only in that, in step (1), sodium monofluorophosphate is replaced with a mixture of phosphorus pentoxide and sodium fluoride in an equal molar ratio of 1:4; the other steps are completely consistent with Example 1.

[0145] Comparative Example 2

[0146] This comparative example provides a phosphorus-carbon anode material, which differs from Example 1 only in that, in step (1), sodium monofluorophosphate is replaced with an equal mass of sodium hypophosphite; the other steps are completely consistent with Example 1.

[0147] Comparative Example 3

[0148] This comparative example provides a phosphorus-carbon anode material. The only difference from Example 1 is that silicon dioxide is no longer added, that is, step (1) is no longer performed, and the mixture in step (2) is directly replaced with an equal mass of sodium monofluorophosphate; the other steps are completely consistent with Example 1.

[0149] Comparative Example 4

[0150] This comparative example provides a phosphorus-carbon anode material, which differs from Example 1 only in that the gas phase coating in step (4) is no longer performed, that is, only a phosphorus-carbon anode material with a first carbon shell is obtained; the other steps are completely consistent with Example 1.

[0151] Test case

[0152] Test samples: phosphorus-carbon anode materials provided in Examples 1-10 and phosphorus-carbon anode materials provided in Comparative Examples 1-4.

[0153] Test Method: Carbon-coated materials were prepared into slurries according to the corresponding phosphorus-carbon anode material sample: carbon black:CMC:SBR = 94:1.5:1.7:2.8, and coated onto aluminum foil. The thickness of the anode coating was 160 μm, resulting in the anode sheet. Then, the anode sheet was assembled with an NFPP cathode and a PP separator to form a sodium-ion battery. The electrolyte was 1 mol / L NaPF6, 40% PC + 60% EMC. The process characteristics and electrochemical performance of the above sodium-ion battery were tested.

[0154] The specific test results are shown in Table 1:

[0155] Table 1

[0156]

[0157] As shown in Table 1, the phosphorus-carbon anode material of the present invention exhibits a core-shell structure with two layers. The core of the phosphorus-carbon anode material includes elemental phosphorus, sodium fluoride, and silicon oxide. Elemental phosphorus is deposited inside the asphalt shell, greatly reducing the expansion effect of the material during cycling. Sodium fluoride can supplement sodium, further improving the material's initial efficiency. Silicon oxide acts as a high-temperature stable material, serving as a framework. The first carbon shell is a stable and uniform carbon layer formed by asphalt, while the second carbon shell is a carbon shell formed by the gaseous encapsulation of an organic carbon source. This reduces the material's specific surface area, improves irreversible surface reactions, and enhances initial efficiency and cycling performance.

[0158] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a phosphorus-carbon anode material, characterized in that, The preparation method includes: Sodium monofluorophosphate, silica, and asphalt are mixed to obtain a mixture; The mixture is subjected to a first sintering and a second sintering in sequence, and the carbon shell layer formed by the decomposition of asphalt is obtained to obtain sintered material one. The first sintered material is subjected to a third sintering process. Sodium monofluorophosphate is first decomposed into phosphorus oxide and sodium fluoride. The phosphorus oxide reacts and deposits with the carbon shell to form elemental phosphorus, thus obtaining the second sintered material. An organic carbon source gas is introduced into the sintered material 2 for gas-phase coating to obtain the phosphorus-carbon anode material; The mixture specifically includes: Sodium monofluorophosphate and silicon dioxide are first mixed to obtain mixture one; then mixture one is mixed with asphalt to obtain mixture two. The mixture, by mass percentage, comprises: 70-90% sodium monofluorophosphate and 10-30% silicon dioxide; The second mixture, by mass percentage, comprises: 75-90% of the first mixture and 10-25% asphalt; The first sintering, second sintering, third sintering, and vapor phase coating are all carried out under a protective gas atmosphere; The temperature of the first sintering is 100~150℃; the time of the first sintering is 0.5~1 h; The temperature of the second sintering is 500~800℃; the time of the second sintering is 2~4 h; The temperature of the third sintering is 800~1200℃; the time of the third sintering is 2~4 h; The organic carbon source gas is a mixture of acetylene and cyclohexane; The flow ratio of acetylene to cyclohexane is (8~5):(2~5); The temperature of the gas phase coating is 600~900℃; the time of the gas phase coating is 0.5~2 h.

2. The method for preparing the phosphorus-carbon anode material according to claim 1, characterized in that, The silicon oxide includes silicon monoxide and / or silicon dioxide.

3. The method for preparing the phosphorus-carbon anode material according to claim 1, characterized in that, The protective gas atmosphere includes any one of nitrogen, argon, or helium.

4. The method for preparing the phosphorus-carbon anode material according to claim 1, characterized in that, The phosphorus oxides include phosphorus pentoxide and / or phosphorus trioxide.

5. The method for preparing the phosphorus-carbon anode material according to claim 1, characterized in that, The total flow rate of the organic carbon source gas is 10~50 mL / min.

6. The phosphorus-carbon anode material prepared by the preparation method according to any one of claims 1 to 5, characterized in that, The phosphorus-carbon anode material exhibits a double-shell core-shell structure; The core of the phosphorus-carbon anode material includes elemental phosphorus, sodium fluoride, and silicon oxide. The double shell includes a first carbon shell and a second carbon shell from the inside out. The first carbon shell is formed by the decomposition of asphalt; the second carbon shell is formed by the gas of an organic carbon source being coated in the gas phase. The core has a particle size of 0.5~5 μm, the first carbon shell has a thickness of 2~10 μm, and the second carbon shell has a thickness of 0.3~1 μm.

7. The application of the phosphorus-carbon anode material according to claim 6 in the preparation of anode sheets or sodium-ion batteries.

8. A negative electrode sheet, characterized in that, The negative electrode sheet includes a metal foil and a negative electrode coating; wherein the negative electrode coating includes the phosphorus-carbon negative electrode material as described in claim 6.

9. A sodium-ion battery, characterized in that, The sodium-ion battery includes the negative electrode as described in claim 8.

Citation Information

Patent Citations

  • Phosphorus-carbon composite negative electrode material and preparation method thereof, negative electrode and sodium ion battery

    CN115832264A

  • Phosphorus-carbon composite material with core-shell structure as well as preparation method and application of phosphorus-carbon composite material

    CN119108524A